Penggunaan teknologi dalam mempermudahkan penghasilan Catan berbentuk 'Representational' - Tay, Sze Eik, (Universiti Malaysia Sarawak (UNIMAS), 2007)
The research is discussing about the uses of technologies nowadays in doing artworks. This research giving up a new differences and renovation to help the artist produces artworks in an easier way. It is also explains how the techniques and the technological medium process were used in producing artworks. However, the focuses on the element and principle of art are still applied.